PENGARUH BREATHING EXERCISE TERHADAP KUALITAS HIDUP LANJUT USIA DI PANTI WERDHA RIA PEMBANGUNAN - Hermansyah Hermansyah; Ratu Karel Lina; Toto Aminoto (Poltekkes Kemenkes Jakarta III, 2015)
Breathing Exercise is a method of breathing in a certain way to improve and enhance theperformance of respiratory system, especially lungs. It turns out that if we do well andregular breathing can stabilize blood pressure and improve respiration.In the elderly oftensuffer respiratory problems due to the elderly decreased organ function, especially lung.This study aims to demonstrate the effect of breathing exercise on quality of life in elderly.The population in this study is the senior citizens who live in Elderly Nursing Ria Development,East Jakarta Cibubur.The sampling technique used was purposive sampling. This is a quasiexperimentalstudy with pre-post test approach design. In this study before the first interventionexamined quality of life.After the intervention was also carried out a similar investigation.Variable quality of life are examined blood pressure, respiration rate, pulse, Barthel indexand VO2max. Before and after the examination results are then compared. By usingparametric paired t test analysis produced t value of 0.505 and the Sign of 0.618, while thevalue t table 1.70. The value of t is greater than t table. It can be concluded that the breathingexercise does not affect the quality of life of the elderly